Planners and Politicians: Liberal Politics and Social Policy 1957-1968 - Arneil, Barbara (Labour / Le Travail, 1999)
The article reviews the book, "Planners and Politicians: Liberal Politics and Social Policy, 1957-1968," by P.E. Bryden.